Evaluation of Development Prospects of Renewable Energy Source for Russia - Nazarova, Yulia Alexandrovna; Sopilko, Natalya Yuryevna; Orlova, Anzhelika Feliksovna; Bolotova, Rimma Shoidorzhievna; Gavlovskaya, Galina Valentinovna (International Journal of Energy Economics and Policy, 2017)
The main mechanisms for supporting renewable energy sources in the wholesale electricity and capacity market, in the retail market and in isolated power systems have been studied. The article analyzes the ecological, social and economic effects of the development of renewable energy in the territory of Russia. Based on official information, the authors gave a quantitative assessment of the effects: increasing export earnings, reducing environmental costs, creating jobs, etc. An integral effect was assessed for the Russian economy from the development of Renewable Energy Source (RES), including various levels of budgets and extra-budgetary funds in the form of duties, taxes and insurance contributions. During the analysis of the development of renewable energy in the territory of Russia, the authors identified the main effects of its use and proposed methods for quantifying the effects determined. The obtained results, like the methodological approaches described in the article, can be used at the federal and regional levels in the development of state support mechanisms for renewable energy, while carrying out technical and economic calculations for projects and programs in the field of renewable resources and energy sources. Keywords: Renewable energy sources, economic effect, ecological effect, social effect, development prospects, energetics of Russia JEL Classifications: O10, Q40, Q41